Сategory "symbol" in context of historical process understanding - Kulabuhov, Vladimir (2018)
In the course of their development, people created a special type of culture, representing a specific world of things, values, symbols, which embodied the image containing an idea. One of the key issues in various scientific fields is the definition of the very concept of "symbol". Nowadays, there is such a scientific discipline as symbol study. The authors of the article suggest to consider the origin and the evolution of the concept "symbol" in the context of historical process understanding. A symbol is one of the key concepts of the humanities and social sciences: the culturology of philosophy, sociology, history, psychology, linguistics, political science, ethnography, aesthetics, etc. During the study they established that symbols played an important role in the whole variety of human culture manifestations - in ideology and religion, politics and law, literature and music, painting and architecture, literature, etiquette, advertising and commerce. In its turn, culture can be represented in the form of a system of different symbols embodying the ideas, the ideals and the meanings by which people live in and which determine the development and the functioning of the culture itself.